384 The risk business of being an entomologist: a systematic review. (24th April 2018) - Stanhope, Jessica; Carver, Scott; Weinstein, Philip
Abstract : Introduction: Adverse work-related health outcomes are a significant problem worldwide. Entomologists, including arthropod breeders, are a unique occupational group exposed to potentially harmful arthropods, pesticides, and other more generic hazards. These exposures may place entomologists at risk of a range of adverse work-related health outcomes. 1 We sought to determine which adverse work-related health outcomes entomologists have experienced, the incidence and prevalence of these outcomes, and what occupational management strategies have been employed by entomologists, and their effectiveness. Methods: A systematic search of eight databases was undertaken to identify studies informing the review objectives. Data pertaining to country, year, design, work-exposure, adverse work-related health outcomes, incidence or prevalence of these outcomes, and occupational management strategies were extracted, and reported descriptively. Result: Results showed entomologists experienced work-related allergies, venom reactions, infections, infestations and delusional parasitosis. These related to exposure to insects, arachnids, chilopods and entognathans, and non-arthropod exposures, e.g. arthropod feed. Few studies reported the incidence or prevalence of such conditions, or work-related management strategies utilised by entomologists. There were no studies that specifically investigated the effectiveness of potential management strategies for entomologists as a population. Critical appraisal indicated poor research quality in this area. Discussion: Entomologists are a diverse, unique occupational group, at risk of a range of adverse work-related health outcomes. This study represents the first systematic review of their work-related health risks. Future studies investigating the prevalence of adverse work-related health outcomes for entomologists, and the effectiveness of management strategies are warranted to decrease the disease burden of this otherwise understudied group. Reference: . Stanhope J, Carver S, Weinstein, P. The risky business of being an entomologist: A systematic review. Environmental Research2015;140:619–633.